Influence of gonadectomy and age at gonadectomy on the risk of developing intervertebral disc herniation in French Bulldogs: a retrospective study - Tabbì, Marco; Troisi, Alessandro; Fugazzotto, Domenico; Marcoccia, Romina; Pettina, Giorgia; Minniti, Simone; Messina, Girolamo; Coppola, Temy; Principato, Gaetano; Arrigo, Federica; Barillaro, Giuseppe; Troiano, Daniele; et al. (Frontiers in Veterinary Science, 2025)
The French Bulldog has become increasingly popular worldwide, but selective breeding for brachycephalic traits has increased its predisposition to several neurological disorders. Among these, intervertebral disc herniation (IVDH) is one of the most common causes of spinal cord compression, pain, and neurological deficits. Although genetic predisposition plays a key role, previous evidence suggests that gonadal hormones factors may also adversely affect skeletal development and spinal biomechanics, thus influencing risk of IVDH. The aim of this study is to evaluate the influence of gonadectomy and age at gonadectomy on the risk of developing IVDH in French Bulldogs. Medical records of 2,101 French Bulldogs were retrospectively reviewed. Dogs with complete clinical and reproductive histories were included and classified into two groups: affected (A group, with IVDH) and control (C group, without IVDH). Early-gonadectomized dogs (<12 months) showed a significantly higher risk of IVDH compared with intact dogs. Early-gonadectomized males were nearly twice as likely to develop IVDH (OR = 1.92) than intact males, while early-gonadectomized females exhibited an even stronger association (OR = 9.84) compared with late-gonadectomized (OR = 2.77) and intact females. The preliminary results of this study suggest a potential influence of gonadectomy and age at gonadectomy on the risk of developing IVDH in French Bulldog. Therefore, the age at which gonadectomy is performed should be carefully considered in this and other predisposed chondrodystrophic breeds. These findings highlight the importance of gonadal hormones and the need for further research to evaluate the differential effects of early age gonadectomy.